2015
DOI: 10.1021/op500379a
|View full text |Cite
|
Sign up to set email alerts
|

Process Development of a GCS Inhibitor Including Demonstration of Lossen Rearrangement on Kilogram Scale

Abstract: A small molecule was under investigation as an inhibitor of glucosylceramide synthase (GCS) for potential use in Fabry disease. To support preclinical activities, a four-step synthesis was developed and used to prepared kilogram quantities of the drug substance. The new route features a scalable CDI-mediated Lossen rearrangement as a substitution for hazardous azide chemistry that was employed in the original route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…9 To gain detailed information, we conducted differential scanning calorimeter (DSC) measurements of benzoyl azide (7) and 3-phenyl-1,4,2-dioxazol-5-one (8). In the temperature range of -20 ~ 100 o C, crystallization temperature (T c ) and melting temperature (T m ) were observed during the first and second cycle of benzoyl azide treatment (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…9 To gain detailed information, we conducted differential scanning calorimeter (DSC) measurements of benzoyl azide (7) and 3-phenyl-1,4,2-dioxazol-5-one (8). In the temperature range of -20 ~ 100 o C, crystallization temperature (T c ) and melting temperature (T m ) were observed during the first and second cycle of benzoyl azide treatment (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Many factors affecting the yield and purity of Curtius rearrangement products have been reported, including reaction kinetics, solvents, ,,,, temperature, ,, calorimetry, , energy release, residence time, , and analytics . We found that the use of toluene provided optimal rearrangement conditions at 85 °C. ,, Because of the potentially explosive and hazardous nature of acyl azide intermediates formed in situ, appropriate concentration of acyl hydrazide, reactor volume and flow, and residence time should be carefully considered to control the energy release.…”
mentioning
confidence: 87%
“…Heat release can be attributed to the decomposition of the acyl azide to form the isocyanate and nitrogen, which is dependent on the concentration of the intermediate and temperature . Differential scanning calorimetry (DSC) indicated that 0.5 M acyl azide releases a heat energy of 187 J/g, while 1 M acyl azide liberates an energy of 364 J/g, which exceeds safety criteria. ,, On the basis of calorimetric data from previous reports, , we chose a hydrazide concentration of 0.1 M, a reactor volume for the Curtius rearrangement of 1.6 mL, and a residence time of 97s, which kept the energy release at a minimum for improved safety. In a flow system, the thermal stability of acyl azides generated in situ is increased through solvent dilution during the flow reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eliglustat tartrate used in these studies was obtained from Genzyme Corporation. Genz-682452 ( 3 , venglustat) was prepared by the method described by Zhao et al…”
Section: Methodsmentioning
confidence: 99%